求微分方程yy'-e^(y^2-2x)=0倒是可以吧yy'看成整体,1/2[y^2]'-e^(y^2-2x)=0令y^2=u得u''/u'=2u'-4,

来源:学生作业帮助网 编辑:六六作业网 时间:2024/07/08 11:50:18
求微分方程yy''-e^(y^2-2x)=0倒是可以吧yy''看成整体,1/2[y^2]''-e^(y^2-2x)=0令y^2=u得u''''/u''=2u''-4,求微分方程yy''-e^(y^2-2x)=0倒是可

求微分方程yy'-e^(y^2-2x)=0倒是可以吧yy'看成整体,1/2[y^2]'-e^(y^2-2x)=0令y^2=u得u''/u'=2u'-4,
求微分方程yy'-e^(y^2-2x)=0
倒是可以吧yy'看成整体,
1/2[y^2]'-e^(y^2-2x)=0
令y^2=u
得u''/u'=2u'-4,

求微分方程yy'-e^(y^2-2x)=0倒是可以吧yy'看成整体,1/2[y^2]'-e^(y^2-2x)=0令y^2=u得u''/u'=2u'-4,
yy'=e^(y^2)e^(-2x)
ye^(-y^2)dy=e^(-2x)dx
e^(-y^2)d(-y^2)=e^(-2x)d(-2x)
积分:e^(-y^2)=e^(-2x)+C